Crosstalk between MiRNAs/lncRNAs and PI3K/AKT signaling pathway in diabetes mellitus: Mechanistic and therapeutic perspectives - Seyed Mohsen Aghaei-Zarch (Non-coding RNA Research, 2024)
Diabetes as a fastest growing diseases worldwide is characterized by elevated blood glucose levels. There’s an enormous financial burden associated with this endocrine disorder, with unequal access to health care between developed and developing countries. PI3Ks (phosphoinositide 3-kinases) have been demonstrated to be crucial for glucose homeostasis, and malfunctioning of these molecules can contribute to an increase in glucose serum levels, the main pathophysiological feature of diabetes. Additionally, recent evidence suggests that miRNAs and lncRNAs are reciprocally interacting with this signaling pathway. It is therefore evident that abnormal regulation of miRNAs/lncRNAs in the lncRNAs/miRNAs/PI3K/AKT axis is related to clinicopathological characteristics and plays a crucial role in the regulation of biological processes. It has therefore been attempted in this review to describe the interaction between PI3K/AKT signaling pathway and various miRNAs/lncRNAs and their importance in DM biology. We also presented the clinical applications of PI3K/AKT-related ncRNAs/herbal medicine in patients with DM.